2015
DOI: 10.1093/asj/sjv170
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, and Clinical Implications of Human Decellularized Adipose Tissue Extracellular Matrix (hDAM): A Comprehensive Review

Abstract: Fat grafting is commonly employed by plastic and reconstructive surgeons to address contour abnormalities and soft-tissue defects; however, because retention rates and thus volume filling effects are unpredictable, there is a search for new and innovative approaches. Initial studies on the use of human decellularized adipose tissue extracellular matrix (hDAM) show promise for its use not only in tissue engineering, but also in fat grafting. In this review, we examine and analyze the literature for the preparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 45 publications
1
40
0
Order By: Relevance
“…Differences however have been noted when stratifying by place of birth where female predominance is increased in those who have immigrated to the US. 26 This difference is speculated to reflect migratory patterns in time where males make up a larger proportion. 27 …”
Section: Demographic Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences however have been noted when stratifying by place of birth where female predominance is increased in those who have immigrated to the US. 26 This difference is speculated to reflect migratory patterns in time where males make up a larger proportion. 27 …”
Section: Demographic Featuresmentioning
confidence: 99%
“…Immigrants to the US with MS reported more vascular risk factors, with hypercholesterolemia being the most common reported comorbid medical problem affecting them compared to US-born individuals ( p = 0.002). 26 A cross-sectional assessment of headache as comorbidity in individuals affected by MS found that chronic migraine was significantly more common among Hispanics (82%) than whites (18%; p = 0.012) and was noted to have significant impact on their daily life activities. 78 Differences in comorbid condition by immigration status in the US Hispanic MS population is expected to be the result of health care disparities that could reflect sociocultural and economic barriers that could have withstanding effects on disability.…”
Section: Potential Risk Factors In Hispanics With Msmentioning
confidence: 99%
“…These cells show less potential than embryonic cells yet compared with bone marrow stem cells, they are easily harvested (55). Lipotransfer seems to improve the structural features of the extracellular matrix and increase its production (57). Histologic assessment after fat transfer revealed new collagen synthesis and dermal hyperplasia with hypervascularity, which was observed locally (55) and in a molecular study, results demonstrated downregulation of fibrotic markers along with upregulation of vasculogenic markers documented using both techniques (58).…”
Section: Fat Grafting and Scarless Wound Healingmentioning
confidence: 99%
“…There is currently a shift toward stromal vascular fraction as a therapeutic for regenerative applications, and we believe that a number of these subpopulations, in addition to the extracellular matrix, act synergistically for regenerative applications. 5,6 We are currently working in earnest to further characterize the differentiation capacity, transcriptional profile, secretome, and clonal properties of mechanically processed adipose-derived stem cells and other constituents of the stromal vascular fraction. We thank you for your letter and look forward to the growing body of knowledge regarding the mechanical processing of adipose tissue and its potential regenerative applications.…”
Section: Sirmentioning
confidence: 99%